2017
DOI: 10.1021/acs.jpclett.7b01989
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Doping Reveals the Importance of Amorphous Chain Rigidity in Charge Transport of Semi-Crystalline Polymers

Abstract: Sequential doping is a promising new doping technique for semicrystalline polymers that has been shown to produce doped films with higher conductivity and more uniform morphology than conventional doping processes, and where the dopant placement in the film can be controlled. As a relatively new technique, however, much work is needed to understand the resulting polymer-dopant interactions upon sequential doping. A combination of infrared spectroscopy and theoretical simulations shows that the dopants selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
143
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(159 citation statements)
references
References 35 publications
16
143
0
Order By: Relevance
“…18 Similar ndings were made by Scholes et al 19 and Chew et al 20 who concluded that the ordered regions of P3HT give rise to a higher chargecarrier mobility and therefore lead to an increase in the electrical conductivity. Here, we explore how the crystallinity inuences the power factor of P3HT vapour-doped with F4TCNQ.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…18 Similar ndings were made by Scholes et al 19 and Chew et al 20 who concluded that the ordered regions of P3HT give rise to a higher chargecarrier mobility and therefore lead to an increase in the electrical conductivity. Here, we explore how the crystallinity inuences the power factor of P3HT vapour-doped with F4TCNQ.…”
supporting
confidence: 52%
“…[18][19][20] By tuning the regioregularity and processing solvent the nanostructure of P3HT could be altered leading to a much higher electrical conductivity. For example, by changing the polymer processing solvent we were able to increase the electrical conductivity from 0.01 to 13 S cm…”
Section: 18mentioning
confidence: 99%
“…While the distribution of counterions in the active layer is straightforward to interpret from Figures and , the precise location of a charge carrier within semicrystalline polymer films remains to be a topic of debate . The lower ionization energy in a crystallite of P3HT has been shown to lead to increased doping efficiency and more delocalized polarons .…”
Section: Resultsmentioning
confidence: 99%
“…The lower ionization energy in a crystallite of P3HT has been shown to lead to increased doping efficiency and more delocalized polarons . Some suggest that a carrier should be in close proximity to its associated counterion, regardless of the carrier concentration . Previously, charge modulation spectroscopy, FTIR, and Raman spectroscopy have been used to study the local environment of polarons in conjugated polymers at low concentrations, typically to determine if holes exist as polarons or bipolarons .…”
Section: Resultsmentioning
confidence: 99%
“…To provide further insight into the PIA spectrum, a modified Holstein Hamiltonian is used to simulate the polaron absorption as previously described, achieving a qualitative fit to the PIA spectrum ( Figure ). Details of the spectral line shape can be found elsewhere . From the simulated spectrum, the number of coherently connected thiophene units in the intrachain direction ( N intra ) can be calculated to be ≈3, consistent with the polaron being localized on single‐coiled chains.…”
Section: Resultsmentioning
confidence: 99%